Government borrowing, money supply, and monetary policy in Nigeria : government's monetary impact in a mixed economy - Ndekwu, Eddy Chicka; Nigerian Institute of Social and Economic Research (Ibadan : Nigerian Institute of Social and Economic Research, 1983)
This book sought to find out the connection between the rate of government borrowing requirements and monetary expansion. It used the United Kingdom and the United States of America as evidence that there was a proof of some positive relationship between the two variables, and suggested that growth in the money supply was rooted in the public sector borrowing requirements.
Bibliography: p. 176-180.
usc 6/7/17
Loans
Keywords: Debts, External; Money supply; Monetary policy; Mixed economy; Nigeria